PELATIHAN PEMBUATAN MINUMAN BUNGA TELANG SEBAGAI PENGENDALI FAKTOR RISIKO COVID-19 PADA KADER POSYANDU LANSIA DI KELURAHAN GEDANGAN - W Wimpy; Enny Listiawati; Oktaviana Puteri Megawati; Shafa Sabela Ramadhani; Sintia Aisyah Nur Said; Yolandita Shintaini Auliya (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Elderly are residents aged 60 years and over.  The determination of 60 years as the baseline for the elderly is because at this age there is a significant physical and physiological decline.  This makes elderly people susceptible to various diseases, including the Corona virus caused by the Sars-Cov-2 virus.  A weakened immune system plus the presence of chronic disease can increase the risk of Corona virus in the elderly.  This study aims to determine the level of knowledge of the people of Gedangan Village , Sukoharjo Regency on the benefits of Bunga Telang as a risk factor for Corona virus control.  The method used is the offline method using the media pre-test and post-test which was held at the Gedangan Village Meeting Hall.  There is a difference with an increasing trend in the post-test scores compared to the pre-test scores in line with the increase in understanding of the extension material of the community service participants. The results of the analysis conducted showed that the level of public knowledge about the benefits of Bunga Telang increased after counseling was carried out.